Un mito tragico nel cuore della Storia: Racconto d’autunno di Tommaso Landolfi - Boillet, Étienne (Amaltea. Revista de Mitocrítica, 2010)
The image of the castle-labyrinth, typical of Gothic literature, finds a central place in Tommaso Landolfi’s Racconto d’autunno (1947). The castle gives shelter to the protagonist, who escapes from the soldiers that pursue him during World War II. Thus, History disappears to reappear only in the end, in a brutal way. Influenced by a Gothic and romantic tradition, the story takes the form of a tragic myth in which the protagonist faces an ancient wound destined to be reopened: thanks to the light of some biographical data, the present study proposes to analyze this mythical and tragic dimension through the attention paid to the theme of the castle-labyrinth, in order to illustrate Landolfi’s work and poetic.